Tradisi Dakwah Kelompok Tarekat “Studi Aktivitas Dakwah Tarekat Syattariyah” - Zainal Zainal (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Islamic preaching development dynamics in West Sumatra there was a different pattern of specific approaches, which use tradition as a means of melt strength values of Islam. Active role Sufi groups can not be separated from using tradition as a powerful media preach Islam in society. Objectivity did missionary show creativity touch his face late missionary by Sufi groups. Although impressed Islamic pattern coloring West Sumatra is Islam